(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
The capacity of eco-friendly biosorbents low cost a biosorbent for methylene blue dye (MBD) removal from wastewater is investigated in this work. In order to assess the potential treatment of industrial aqueous solutions by Activated Carbon, Palm leaf and Pomegranate peel, a series of laboratory batch flow experiments were conducted . Batch studies were carried out to investigate the effects of pH dye solution, contact time, biosorbent dosage, beginning dye concentration, and rotational speed on MBD biosorption at room temperature. The optimal parameters for MBD removal by Activated Carbon, Palm leaf, and Pomegranate peel were determined to be pH 5 and 1 g/100 ml dye solution, 120 min contact time for MBD concentration of 100 mg/l, and agitation speed of 250 rpm. The experimental data were analyzed using Langmuir and Freundlich isotherm models. The Langmuir biosorption isotherm was found to be the best model for simulation of MBD bisorption into Activated Carbon, Palm leaf and Pomegranate peel , with the Langmuir constant linked to the biosorption ability (qmax) of 7.87, 2.78 and 2.33 mg/g and a coefficient of determination (R2) of 0.9996, 0.9985 and 0.9999 for Activated Carbon, Palm leaf and Pomegranate pee. The results indicate that activated carbon is the best environmentally friendly bio-adsorbent used in this study, which can be used efficiently to remove methylene blue dye from aqueous solutions.